Use of Medihoney as a non-surgical therapy for chronic pressure ulcers in patients with spinal cord injury - Biglari, Bahram; Gerner, Hans-Jürgen (Spinal cord, 2012)
Study design:Prospective, observational study of 20 spinal cord-injured (SCI) patients with chronic pressure ulcers (PUs) using Medihoney.Objectives:To determine the effects of Medihoney by bacterial growth, wound size and stage of healing in PUs.Methods:We treated 20 SCI adult patients with chronic PUs using Medihoney. In all, 7 patients (35%) were female, and 13 (65%) were male. The average patient age was 48.7 years (30-79). In all, 6 patients (30%) were tetraplegic and 14 (70%) were paraplegic. Also, 5 patients (25%) had grade IV ulcers and 15 patients (75%) had grade III ulcers according to the National Pressure Ulcer Advisory Panel.Results:After 1 week of treatment with Medihoney, all swabs were void of bacterial growth. Overall 18 patients (90%) showed complete wound healing after a period of 4 weeks, and the resulting scars were soft and elastic. No negative effects were noted from the treatment using Medihoney. No blood sugar level derailment was documented.Conclusion:The medical-honey approach to wound care must be part of a comprehensive conservative surgical wound-care concept. Our study indicates the highly valuable efficacy of honey in wound management and infection control as measured by bacterial growth, wound size and healing stage.